Working Capital Management of Larsen & Turbo - K. Pavithra; S.Kirubadevi (International Journal of Engineering and Management Research, 2018)
The goal of working capital management is to ensure that the firm is able to continue its operations and that it has sufficient cash flow to satisfy both maturing short-term debt and upcoming operational expenses. The current study has concentrated on analysing the working capital management of Larsen & Turbo Company based on their liquidity, profitability positions and cash flow statements over a decade. The study is based on secondary data collected from the financial reports published in the official websites of the company for a period of thirteen years from 2003-04 to 2015-16. The data have been analyzed using the financial and statistical tools namely Ratio Analysis, cash flow and Correlation Analysis. It has been found that the working capital management of Larsen & Turbo is good and the company has to improve its turnover ratios in the future.